Epidemiological Study on Mycoplasma pneumoniae and Chlamydia pneumoniae Infection of Hospitalized Children in a Single Center During the COVID-19 Pandemic - Cai, Fengqing; Shou, Xinyi; Ye, Qing (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Since the outbreak of COVID-19, a series of preventive and control measures in China have been used to effectively curb the spread of COVID-19. This study aimed to analyze the epidemiological characteristics of Mycoplasma pneumoniae (MP) and Chlamydia pneumoniae (CP) in hospitalized children with acute respiratory tract infection during the COVID-19 pandemic. Methods: MP IgM antibody and CP IgM antibody were detected in all hospitalized children due to acute respiratory tract infection in the Children's Hospital Affiliated to Zhejiang University from January 2019 to December 2020. These data were compared between 2019 and 2020 based on age and month. Results: The overall detection rate of MP and CP in 2020 was significantly lower than that in 2019 (MP: 21.5% vs 32.9%, P<0.001; CP: 0.3% vs 0.9%, P<0.001). This study found a 4-fold reduction in the number of children positive for MP and a 7.5-fold reduction in the number of children positive for CP from 2019 to 2020. The positive cases were concentrated in children aged >1-year-old. In 2019, the positive rate of MP was detected more commonly in children 3 years of age or older than in younger children. In 2020, the higher positive rate of MP reached a peak in the 3- to 6-year age group (35.3%). CP was detected predominantly in children aged 6 years older in 2019 and 2020, with positive rates of 4.8% and 2.6%, respectively. Meanwhile, the positive rates of MP in 2019 were detected more commonly in July, August and September, with 47.2%, 46.7% and 46.3%, respectively. Nevertheless, the positive rates of MP from February to December 2020 apparently decreased compared to those in 2019. The positive rates of CP were evenly distributed throughout the year, with 0.5%-1.6% in 2019 and 0.0%-2.1% in 2020. Conclusions: A series of preventive and control measures for SARS-CoV-2 during the COVID-19 pandemic not only contain the spread of SARS-CoV-2 but also sharply improve the infection of other atypical pathogens, including MP and CP.